Identification and storage of plastics in libraries and archives. (June 2022) - Stein, Chantal; Pace, Jessica; McCann, Laura
The safe storage and handling of plastic objects presents a pressing and often overlooked problem in many library and archival collections. Plastics are notoriously difficult to care for because they can deteriorate faster than other materials in archival collections. The so-called "malignant" plastics can also produce harmful degradation products that damage surrounding materials, including photographs and papers. Part of the issue is the myriad available tools for plastics identification, which can be both cumbersome and daunting. The other is that ideal storage environments for plastics recommended in the preservation literature are often difficult to achieve due to the accessibility needs and space constraints faced by many libraries and archives. This article introduces a current project at New York University Libraries that evaluates existing recommendations for the identification and housing of plastics, and provides guidelines for making scalable housing types that support user access.